2022
DOI: 10.1155/2022/7608712
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of EZH2/miR-138-5p Axis Contributes to Radiosensitivity in Hepatocellular Carcinoma Cell by Downregulating Hypoxia-Inducible Factor 1 Alpha (HIF-1α)

Abstract: Enhancer of zeste homolog 2 (EZH2) is a histone methyltransferase involved in cell proliferation, invasion, angiogenesis, and metastasis in various cancers, including hepatocellular carcinoma (HCC). However, the role and molecular mechanisms of EZH2 in HCC radiosensitivity remain unclear. Here, we show that EZH2 is upregulated in HCC cells and the aberrantly overexpressed EZH2 is associated with the poor prognosis of HCC patients. Using miRNA databases, we identified miR-138-5p as a regulator of EZH2. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…MiR‐138‐5p was characterized as a tumor suppressor in bladder cancer, 16 , 17 colorectal cancer, 18 breast cancer, 19 and hepatocellular carcinoma. 20 , 21 To determine the diagnostic value of miR‐138‐5p as a biomarker of lung cancer, we investigated miR‐138‐5p expression in 18 lung cancer serum samples and matched adjacent normal serum samples through qRT‐PCR. The miR‐138‐5p expression was significantly reduced in the lung cancer serum samples compared with normal controls ( p < 0.001) (Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…MiR‐138‐5p was characterized as a tumor suppressor in bladder cancer, 16 , 17 colorectal cancer, 18 breast cancer, 19 and hepatocellular carcinoma. 20 , 21 To determine the diagnostic value of miR‐138‐5p as a biomarker of lung cancer, we investigated miR‐138‐5p expression in 18 lung cancer serum samples and matched adjacent normal serum samples through qRT‐PCR. The miR‐138‐5p expression was significantly reduced in the lung cancer serum samples compared with normal controls ( p < 0.001) (Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of miR-138-5 significantly suppresses the expression level of HIF-1α ( Bai et al, 2022 ). Additionally, it has been demonstrated the protective effect of miR-138-5 on cardiovascular damage due to the inhibition of aldosterone synthase (CYP11B2) leading to reversal of cardiac fibrotic remodeling ( Kim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mRNA risk signature we constructed has an essential effect on the prognosis and development of HCC. Previous studies have shown that seven mRNAs in the mRNA risk signature can act as oncogenes to promote HCC progression, including PPM1G [ 39 ], PHOSPHO2 [ 40 ], YBX1 [ 41 ], PSRC1 [ 42 ], UCK2 [ 43 ], EZH2 [ 44 ], and CDCA8 [ 45 ]. However, MEX3A, TAF3, TMEM69, and DYNC1LI1 have not been experimentally studied in HCC.…”
Section: Discussionmentioning
confidence: 99%